Legal Protection of Inventor Employees through Patent Ownership Agreements in Indonesia - Khairunnisa Rahimah; Muhammad Amirulloh; Kilkoda Agus Saleh (Universitas Muhammadiyah Sumatera Utara, 2022)
Intellectual property born in the production process in a company is usually a patent produced by inventor employees through research and development activities. However, arrangements regarding the ownership of patents generated by inventor employees in employment or service relations in Article 12 and Article 13 of the Patent Law grant the patent ownership rights automatically to the employer so as not to provide adequate legal protection to the inventor employee. Legal protection for an employed inventor is important to note because it will spur IPR productivity and motivate inventors' creativity to produce intellectual property work. This research used normative juridical methods with analytical descriptive research specifications. Data collection was done through interviews together with company representatives at PT. Martina Berto (Tbk) and PT. Bio Farma (Persero). The results showed that the practice of patent ownership produced by inventor employees at PT. Martina Berto (Tbk) and PT. Bio Farma (Persero) based on Article 12 and Article 13 of the Patent Law is contrary to the principle of alter ego. Inventor employees can negotiate with the company by forming a patent ownership agreement that will clarify the ownership rights and the number of rewards that will be obtained by inventor employees based on Article 12 paragraph (1) and Article 153 of the Patent Law